Upaya Meningkatkan Kemampuan Siswa Menulis Laporan Perjalanan Melalui Metode Group Investigation - Faeliati Waruwu (JURNAL GLOBAL EDUKASI, 2020)
Abstract: The research objective is to find out the improvement in students' ability to write travel reports using the Group Investigation method. The method used in the study is the Group Investigation method. The results of the study were the first cycle, the average student learning outcomes were 68.12, the percentage of students completeness was 37.75%, and the percentage of students completeness was 62.50%. For the results of the second cycle, the average student learning outcomes reached 83.12, the percentage of students completeness reached 100%, and the percentage of incompleteness reached 0%. Therefore, the percentage of completeness has reached the target, so the study is limited to cycle II. Based on the results of this study, the researchers suggest that teachers apply the Group Investigation learning method in each subject in order to provide new variations in the learning process in an effort to achieve the expected learning goals. Keywords: writing, travel report, group investigation Abstrak: Tujuan penelitian yaitu untuk mengetahui peningkatan kemampuan siswa menulis laporan perjalanan dengan menggunakan metode Group Investigation. Metode yang digunakanan pada penelitian adalah metode Group Investigation. Adapun hasil dari penelitian adalah siklus I, rata-rata hasil belajar siswa sebesar 68,12, persentase ketuntasan siswa sebesar 37,75%, dan persentase ketidaktuntasan siswa sebesar 62,50%. Untuk hasil siklus II, rata-rata hasil belajar siswa mencapai 83,12, persentase ketuntasan siswa mencapai 100%, dan persentase ketidaktuntasan mencapai 0 %. Oleh karena itu, persentase ketuntasan telah mencapai target maka penelitian dibatasi pada siklus II. Berdasarkan hasil penelitian ini, maka peneliti menyarankan supaya guru menerapkan metode pembelajaran Group Investigation pada setiap mata pelajaran agar dapat memberikan variatif baru dalam proses pembelajaran sebagai upaya untuk tercapainya tujuan pembelajaran yang diharapkan. Kata kunci: menulis, laporan perjalanan, group investigation